STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - Setiawan, Yahya; Sugiatno, Sugiatno; Karolina, Asri (INCARE, International Journal of Educational Resources, 2020)
This study aimed at finding out a depiction of the strategies applied by the Islamic Education teacher in shaping religious character in SKMN 2 Rejang Lebong. This study deployed a qualitative approach with the Islamic Education teacher as the primary informant, while the secondary informants referred to several teachers of other scholastic subjects at SMKN 2 Rejang Lebong. To obtain information as desirable, observation and interview techniques were used. After the data were collected, analysis was carried out by referring to Milse’s et al theory, namely: data reduction, data presentation, and conclusion drawing. This study revealed hat in shaping students’ religious character, the Islamic Education teacher ran three programs including: performing compulsory prayers and sunnah in congregation at school, mentoring, and lecturing training. The supporting factor of such activities was that they were supported by the principal and other teachers. The obstacle faced was sometimes related to the existence of several students who did not have good familial backgrounds so they were very difficult to be managed and directed by the teacher.